Gender perspective: perceptions by pre-school education program students of a Chilean regional university - Narváez-Prosser, Lilian; Sanzana-Vallejos, Gloria; Corrales-Huenul, Angélica; Soto-Hernández, Valentina; Garcés-Bustamante, José Luis; Ferrada-Montecinos, Yasna Patricia (Frontiers in Education, 2025)
The aim of this study was to analyze perceptions on gender, sexist practices and stereotypes by Pre-School Education program students in the context of pre-school classrooms. To this end, we carried out a mixed method interpretative research based on the case study of the Pre-School Education program of a regional University in Chile. For this purpose, we carried out a documentary analysis of the program’s curriculum, as well as a Likert-type ad-hoc survey, a purposive sample comprising 45 students from different cohorts and a focus group of informant students in the framework of progressive internship courses. The main results suggest the inclusion of gender issues to the profile of a graduate of the program, as well as transversally in the courses of the curriculum. There is no significant association of knowledge regarding gender equality and sexual-gender differences in the courses the students were attending. In fact, the students suggest there is a need for further practical training in order to transfer such learning into the classroom. Additionally, there is an agreement among students regarding the significance of including gender perspective for Pre-School Education students. Lastly, the discussion regarding experiences in pre-school classrooms show that students are able to recognize gender stereotypes in games, toys and colors, among others.